Why the End Is Here for State Death Transfer Taxes and How States Should Respond - Jenny L. Juehring (Washington University Law Review, 2019)
The remaining states with a death transfer tax should begin the process of repeal. Some state death transfer taxes have rates that give preferential treatment to bequests that are likely on the decline due to changes in household structure. State death transfer taxes, as a result of interstate competition, give incentives to people to move states, underreport death transfers, and use other tactics to avoid a state death transfer tax. State death transfer taxes are failing to be a significant source of state revenue. Additionally, state death transfer taxes cannot be an effective tool to combat wealth inequality. Without any justification and serving no purpose, the state death transfer tax is at its end.
Keywords: State death transfer taxes; State taxes; Tax law; Estate tax; Death transfers